The Effect of Organizational Learning on Organizational Commitment, Job Satisfaction and Work Performance - Ong, Gua Pak (2007)
Currently, it is widely believed that organizational learning is the best approach to improve organizational work outcomes such as employees work performance, job satisfaction, organizational commitment etc. Organizational learning is no longer exclusive to the private sector and it is increasingly emerging as an important strategy in the public service sector. The purpose of this study is to examine the effect of organizational learning, organizational commitment and job satisfaction on work performance among the public service managers. In addition, this study seeks to determine the role of organizational commitment and job satisfaction as mediator on the relationship between organizational learning and public service managers' work performance. The population of the study is around 4579 Administrative and Diplomatic (ADS) officers working in 28 ministries located in the Federal Territory of Kuala Lumpur and Putrajaya. The collection of primary data was through the distribution of personally administered questionnaires to the respondents who were chosen by systematic sampling procedure. A total of 435 (87%) answered questionnaires were returned and used in the final analysis. Instruments used in this study are organizational learning (Gomez et a/., 2001), organizational commitment (Porter et a/., 1974), job satisfaction - - - 4 --..-,-=,--...-*--. ..*.-I. r-ui - r---------c----- - - ----- " - .- (Hackman and Oldham, 1975) and work performance (Suliman, 2001). Exploratory Data Analysis (EDA) was conducted on the data and the results met the basic assumptions of normality and linearity. Cronbanch Alpha and Confirmatory Factor Analysis (CFA) were used to test the reliability and validity of the instruments respectively and they indicated acceptable results. The Pearson correlation, regression and path analysis were employed to obtain the answers for the research questions to achieve the objectives of the study. The findings indicate that the level of organizational learning, organizational -.,. , . . commitment, job satisfaction and work performance are rather high among the ADS officers. Organizational learning is positively related to organizational commitment, job satisfaction, and work performance among the public service managers. Organizational commitment and job satisfaction are also positively related with work performance and these variables partially mediate the relationship between organizational learning and work performance. Organizational learning is equally important in explaining organizational commitment, job satisfaction and work performance. At the same time, organizational learning, job satisfaction and organizational commitment are also equally important in explaining work performance among the public service managers. In conclusion, this study contributes and enriches present knowledge in this field and it can be argued that western theories can be valid in non-western setting. The implications of the findings of this study are that top management in ministries need to pay serious attention and effort to create a conducive environment that will encourage learning among the employees. This will improve work outcomes and consequently improve the government delivery system.